Prevalence and consequences of microplastic ingestion in the world's southernmost insect, Belgica antarctica - Jack J. Devlin; Cleverson Lima; Yuta Kawarasaki; J.D. Gantz; Vitor A.C. Pavinato; Marco Scaramelli; Valentina Ferrari; Lisa Vaccari; Giovanni Birarda; Elisa Bergami; Andrew P. Michel; Peter Convey; et al. (Science of The Total Environment, 2025)

Dosimetric comparison of proton therapy and CyberKnife in stereotactic body radiation therapy for liver cancers - Samuel Shyllon; Scott Penfold; Ray Dalfsen; Elsebe Kirkness; Ben Hug; Pejman Rowshanfarzad; Peter Devlin; Colin Tang; Hien Le; Peter Gorayski; Garry Grogan; Rachel Kearvell; et al. (Physical and Engineering Sciences in Medicine, 2024)
Stereotactic body radiation therapy (SBRT) has been increasingly used for the ablation of liver tumours. CyberKnife and proton beam therapy (PBT) are two advanced treatment technologies suitable to deliver SBRT with high dose conformity and steep dose gradients. However, there is very limited data comparing the dosimetric characteristics of CyberKnife to PBT for liver SBRT. PBT and CyberKnife plans were retrospectively generated using 4DCT datasets of ten patients who were previously treated for hepatocellular carcinoma (HCC, N = 5) and liver metastasis ( N = 5). Dose volume histogram data was assessed and compared against selected criteria; given a dose prescription of 54 Gy in 3 fractions for liver metastases and 45 Gy in 3 fractions for HCC, with previously published consensus-based normal tissue dose constraints. Comparison of evaluation parameters showed a statistically significant difference for target volume coverage and liver, lungs and spinal cord ( p < 0.05) dose, while chest wall and skin did not indicate a significant difference between the two modalities. A number of optimal normal tissue constraints was violated by both the CyberKnife and proton plans for the same patients due to proximity of tumour to chest wall. PBT resulted in greater organ sparing, the extent of which was mainly dependent on tumour location. Tumours located on the liver periphery experienced the largest increase in organ sparing. Organ sparing for CyberKnife was comparable with PBT for small target volumes.

Refining the in vitro release test method for a dapivirine-releasing vaginal ring to match in vivo performance - Diarmaid J. Murphy; Deanna Lim; Ryan Armstrong; Clare F. McCoy; Yahya H. Dallal Bashi; Peter Boyd; Tiffany Derrick; Patrick Spence; Bríd Devlin; R. Karl Malcolm (Drug Delivery and Translational Research, 2023)
Previously reported in vitro release test methods for drug-releasing vaginal rings containing poorly water-soluble drugs have described use of water-alcohol systems or surfactant solutions in efforts to maintain sink conditions. Here, as part of efforts to more closely match in vitro and in vivo release for the 25 mg dapivirine matrix-type silicone elastomer vaginal ring for HIV prevention, we have investigated alternatives to the 1:1 v/v water/isopropanol medium described previously. Specifically, we evaluated dapivirine release from rings into (i) monophasic water/isopropanol mixtures of varying compositions and (ii) biphasic buffer/octanol systems using pH 4.2 and pH 7.0 buffers. The rate and mechanism of dapivirine release were dependent upon the isopropanol concentration in the release medium, in accordance with the observed trend in drug solubility. At 0 and 10% v/v isopropanol concentrations, dapivirine release followed a partition-controlled mechansim. For media containing ≥ 20% v/v isopropanol, in vitro release of dapivirine was significantly increased and obeyed permeation-controlled kinetics. Cumulative release of ~3.5 mg dapivirine over 28 days was obtained using a water isopropanol mixture containing 20% v/v isopropanol, similar to the ~4 mg dapivirine released in vivo. Dapivirine release into the biphasic buffer/octanol system (intended to mimic the fluid/tissue environment in vivo) was constrained by the limited solubility of dapivirine in the buffer component in which the ring resided, such that cumulative dapivirine release was consistently lower than that observed with the 20% v/v isopropanol in water medium. Release into the biphasic system was also pH dependent, in line with dapivirine’s pK a and with potential implications for in vivo release and absorption in women with elevated vaginal pH. Graphical abstract

NEOTROPICAL ALIEN MAMMALS: a data set of occurrence and abundance of alien mammals in the Neotropics - Clarissa Alves da Rosa; Bruno R. Ribeiro; Vanesa Bejarano; Fernando Henrique Puertas; Adriana Bocchiglieri; Adriana Loeser dos Santos Barbosa; Adriano Garcia Chiarello; Adriano Pereira Paglia; Adriele Aparecida Pereira; Adryelle Francisca de Souza Moreira; Agnis Cristiane de Souza; Aiesca Pellegrin; et al. (Ecology, 2020)
Biological invasion is one of the main threats to native biodiversity. For a species to become invasive, it must be voluntarily or involuntarily introduced by humans into a nonnative habitat. Mammals were among first taxa to be introduced worldwide for game, meat, and labor, yet the number of species introduced in the Neotropics remains unknown. In this data set, we make available occurrence and abundance data on mammal species that (1) transposed a geographical barrier and (2) were voluntarily or involuntarily introduced by humans into the Neotropics. Our data set is composed of 73,738 historical and current georeferenced records on alien mammal species of which around 96% correspond to occurrence data on 77 species belonging to eight orders and 26 families. Data cover 26 continental countries in the Neotropics, ranging from Mexico and its frontier regions (southern Florida and coastal‐central Florida in the southeast United States) to Argentina, Paraguay, Chile, and Uruguay, and the 13 countries of Caribbean islands. Our data set also includes neotropical species (e.g., Callithrix sp., Myocastor coypus , Nasua nasua) considered alien in particular areas of Neotropics. The most numerous species in terms of records are from Bos sp. ( n = 37,782), Sus scrofa ( n = 6,730), and Canis familiaris ( n = 10,084); 17 species were represented by only one record (e.g., S yncerus caffer, Cervus timorensis, Cervus unicolor, Canis latrans ). Primates have the highest number of species in the data set ( n = 20 species), partly because of uncertainties regarding taxonomic identification of the genera Callithrix, which includes the species Callithrix aurita, Callithrix flaviceps, Callithrix geoffroyi, Callithrix jacchus, Callithrix kuhlii, Callithrix penicillata , and their hybrids. This unique data set will be a valuable source of information on invasion risk assessments, biodiversity redistribution and conservation‐related research. There are no copyright restrictions. Please cite this data paper when using the data in publications. We also request that researchers and teachers inform us on how they are using the data.

NEOTROPICAL XENARTHRANS: a data set of occurrence of xenarthran species in the Neotropics - Paloma Marques Santos; Adriana Bocchiglieri; Adriano Garcia Chiarello; Adriano Pereira Paglia; Adryelle Moreira; Agnis Cristiane de Souza; Agustin Manuel Abba; Agustin Paviolo; Ailin Gatica; Akyllan Zoppi Medeiro; Alan Nilo Costa; Alberto Gonzalez Gallina; et al. (Ecology, 2019)
Xenarthrans—anteaters, sloths, and armadillos—have essential functions for ecosystem maintenance, such as insect control and nutrient cycling, playing key roles as ecosystem engineers. Because of habitat loss and fragmentation, hunting pressure, and conflicts with domestic dogs, these species have been threatened locally, regionally, or even across their full distribution ranges. The Neotropics harbor 21 species of armadillos, 10 anteaters, and 6 sloths. Our data set includes the families Chlamyphoridae (13), Dasypodidae (7), Myrmecophagidae (3), Bradypodidae (4), and Megalonychidae (2). We have no occurrence data on Dasypus pilosus (Dasypodidae). Regarding Cyclopedidae, until recently, only one species was recognized, but new genetic studies have revealed that the group is represented by seven species. In this data paper, we compiled a total of 42,528 records of 31 species, represented by occurrence and quantitative data, totaling 24,847 unique georeferenced records. The geographic range is from the southern United States, Mexico, and Caribbean countries at the northern portion of the Neotropics, to the austral distribution in Argentina, Paraguay, Chile, and Uruguay. Regarding anteaters, Myrmecophaga tridactyla has the most records ( n = 5,941), and Cyclopes sp. have the fewest ( n = 240). The armadillo species with the most data is Dasypus novemcinctus ( n = 11,588), and the fewest data are recorded for Calyptophractus retusus ( n = 33). With regard to sloth species, Bradypus variegatus has the most records ( n = 962), and Bradypus pygmaeus has the fewest ( n = 12). Our main objective with Neotropical Xenarthrans is to make occurrence and quantitative data available to facilitate more ecological research, particularly if we integrate the xenarthran data with other data sets of Neotropical Series that will become available very soon (i.e., Neotropical Carnivores, Neotropical Invasive Mammals, and Neotropical Hunters and Dogs). Therefore, studies on trophic cascades, hunting pressure, habitat loss, fragmentation effects, species invasion, and climate change effects will be possible with the Neotropical Xenarthrans data set. Please cite this data paper when using its data in publications. We also request that researchers and teachers inform us of how they are using these data.

Jaguar movement database: a GPS‐based movement dataset of an apex predator in the Neotropics - Ronaldo G. Morato; Jeffrey J. Thompson; Agustin Paviolo; Jesus A. de La Torre; Fernando Lima; Roy T. McBride; Rogerio C. Paula; Laury Cullen; Leandro Silveira; Daniel L. Z. Kantek; Emiliano E. Ramalho; Louise Maranhão; et al. (Ecology, 2018)
The field of movement ecology has rapidly grown during the last decade, with important advancements in tracking devices and analytical tools that have provided unprecedented insights into where, when, and why species move across a landscape. Although there has been an increasing emphasis on making animal movement data publicly available, there has also been a conspicuous dearth in the availability of such data on large carnivores. Globally, large predators are of conservation concern. However, due to their secretive behavior and low densities, obtaining movement data on apex predators is expensive and logistically challenging. Consequently, the relatively small sample sizes typical of large carnivore movement studies may limit insights into the ecology and behavior of these elusive predators. The aim of this initiative is to make available to the conservation‐scientific community a dataset of 134,690 locations of jaguars ( Panthera onca ) collected from 117 individuals (54 males and 63 females) tracked by GPS technology. Individual jaguars were monitored in five different range countries representing a large portion of the species’ distribution. This dataset may be used to answer a variety of ecological questions including but not limited to: improved models of connectivity from local to continental scales; the use of natural or human‐modified landscapes by jaguars; movement behavior of jaguars in regions not represented in this dataset; intraspecific interactions; and predator‐prey interactions. In making our dataset publicly available, we hope to motivate other research groups to do the same in the near future. Specifically, we aim to help inform a better understanding of jaguar movement ecology with applications towards effective decision making and maximizing long‐term conservation efforts for this ecologically important species. There are no costs, copyright, or proprietary restrictions associated with this data set. When using this data set, please cite this article to recognize the effort involved in gathering and collating the data and the willingness of the authors to make it publicly available.

Vulnerability of the Great Barrier Reef to climate change and local pressures - Nicholas H. Wolff; Peter J. Mumby; Michelle Devlin; Kenneth R. N. Anthony (Global Change Biology, 2018)
Australia's Great Barrier Reef ( GBR ) is under pressure from a suite of stressors including cyclones, crown‐of‐thorns starfish ( COTS ), nutrients from river run‐off and warming events that drive mass coral bleaching. Two key questions are: how vulnerable will the GBR be to future environmental scenarios, and to what extent can local management actions lower vulnerability in the face of climate change? To address these questions, we use a simple empirical and mechanistic coral model to explore six scenarios that represent plausible combinations of climate change projections (from four Representative Concentration Pathways, RCP s), cyclones and local stressors. Projections (2017–2050) indicate significant potential for coral recovery in the near‐term, relative to current state, followed by climate‐driven decline. Under a scenario of unmitigated emissions ( RCP 8.5) and business‐as‐usual management of local stressors, mean coral cover on the GBR is predicted to recover over the next decade and then rapidly decline to only 3% by year 2050. In contrast, a scenario of strong carbon mitigation ( RCP 2.6) and improved water quality, predicts significant coral recovery over the next two decades, followed by a relatively modest climate‐driven decline that sustained coral cover above 26% by 2050. In an analysis of the impacts of cumulative stressors on coral cover relative to potential coral cover in the absence of such impacts, we found that GBR ‐wide reef performance will decline 27%–74% depending on the scenario. Up to 66% of performance loss is attributable to local stressors. The potential for management to reduce vulnerability, measured here as the mean number of years coral cover can be kept above 30%, is spatially variable. Management strategies that alleviate cumulative impacts have the potential to reduce the vulnerability of some midshelf reefs in the central GBR by 83%, but only if combined with strong mitigation of carbon emissions.

Infanticide in a jaguar (Panthera onca) population—does the provision of livestock carcasses increase the risk? - Fernando R. Tortato; Allison L. Devlin; Rafael Hoogesteijn; Joares A. May Júnior; Jacqueline L. Frair; Peter G. Crawshaw; Thiago J. Izzo; Howard B. Quigley (acta ethologica, 2017)

Repositioning the hereditary paraganglioma critical region on chromosome band 11q23 - B. E. Baysal; E. M. van Schothorst; Joan E. Farr; P. Grashof; David Myssiorek; Wendy S. Rubinstein; Peter Taschner; Cees J. Cornelisse; B. Devlin; Peter Devilee; C. W. Richard III. (Human Genetics, 1999)

The Brassica rapa elongated internode (EIN) gene encodes phytochrome B - Paul F Devlin; David E Somers; Peter H Quail; Garry C Whitelam (Plant Molecular Biology, 1997)